Sistem Pakar Kombinasi Metode Certainty Factor dan Dempster Shafer - Nelly Astuti Hasibuan; Alwin Fau (Journal of Information System Research (JOSH), 2022)
An expert system is a technique of artificial intelligence that uses certainty techniques to solve problems. There are several techniques that can be used to solve the problem of uncertainty, including the certainty factor method and the mathematical theory of Dempster Shafer. Both methods and techniques can be applied to solve expert system problems. However, each method has advantages and disadvantages in determining the diagnosis. In the expert system, there are 2 values ​​used for the diagnosis process, including the expert value taken from the expert hypothesis and the user value or evidence which is the value obtained based on the facts of an event. Dempster Shafer theory can only use the evidence value in determining the density value, while the certainty factor method can use evidence and hypothesis values. Thus, the combination made to overcome the weakness of one method by using the advantages of the other method is expected to produce a better certainty value.